Multi-Locus Phylogeny and Taxonomy of the Fungal Complex Associated With Rusty Root Rot of Panax ginseng in China - Guan, Yi Ming; Ma, Ying Ying; Jin, Qiao; Wang, Qiu Xia; Liu, Ning; Fu, Yong Ping; Zhang, Ya Yu; Li, Yu (Frontiers in Microbiology, 2020)
Panax ginseng rusty root rot caused by the Ilyonectria species complex is a devastating disease, and it is one of the main factors contributing to the difficulty in continual cropping. Rusty root rot occurs in all ginseng fields, but little is known about the taxonomy of the fungal pathogen complex, especially Ilyonectria and Ilyonectria-like species. Rusty root rot samples were collected from commercial ginseng cultivation areas of China, and the pathogens were isolated and purified as single spores. Based on the combination analysis of multiple loci (rDNA-ITS, TUB, HIS3, TEF, ACT, LSU, RPB1, RPB2, and SSU) and morphological characteristics, the pathogens causing ginseng rusty root rot were determined. Fungal isolates were obtained from infected roots in 56 locations within main cultivation areas in China. A total of 766 strains were identified as Ilyonectria, Ilyonectria-like and Rhexocercosporidium species, including I. robusta (55.0%), I. communis (21.7%), I. mors-panacis (10.9%), I. pseudodestructans (2.0%), I. changbaiensis (1.3%), I. qitaiheensis (1.3%), Neonectria obtusispora (2.0%), Dactylonectria torresensis (0.5%), D. sp. (0.5%), and R. panacis (1.5%), and four novel species, Thelonectria ginsengicola (1.0%), T. jixiensis (1.0%), T. mulanensis (0.8%) and T. fusongensis (0.5%), with a total of 14 species. As the pathogen present in the highest proportion, I. robusta was the most prevalent and damaging species, unlike the pathogens reported previously. All of the examined strains were proven to cause ginseng rusty root rot. Our results indicate that the taxonomy of the fungal complex associated with ginseng rusty root rot includes Ilyonectria, Ilyonectria-like genera (Dactylonectria, Neonectria, and Thelonectria) and Rhexocercosporidium.